La Administración de Riesgos Empresariales (2019)
Enterprises today are constantly exposed to constant risks that can affect the fulfillment of their mission and their institutional objectives. Under these circunstances, Enterprise Risk Management provides the entities with the necessary means to identify the risks that may arise, measure their magnitude and define a way of responding to them so they will not affect the interests, patrimony and responsibility of the organization.Under the decided support of the general management, who is ultimately responsible for risk administration within the company, Enterprise Risk Management engages all employees in its purpose and includes all the processes in the entity.